Estetika dalam Penerjemahan Novel Bahasa Jepang : Perspektif Dekonstruksi - Laksana, Ketut Gede Adi Putra; Setiawan, Teguh; Rohali (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
The translation of Japanese novels into Indonesian faces challenges in maintaining their distinctive aesthetic values. Japanese aesthetics often contain unique concepts such as mono no aware and wabi-sabi, which do not always have direct equivalents in Indonesian. This study aims to identify 11 data points of aesthetic value changes in the translation process of the novel Diary of A Void using Derrida's (1978) deconstruction approach. By applying Derrida's deconstruction theory (1978) and Venuti's translation theory (1995), this research aims to uncover the forms of meaning and style shifts in the translated novel Diary of Void. Data were collected through textual analysis of both the original novel and the translation, focusing on diction, language style, and aesthetic representation. The research results show that there are significant changes in aesthetic value, particularly in symbolic expressions and the use of metaphors that have undergone domestication. These findings indicate that there is a negotiation of meaning by the translator to adjust to the target cultural context. Through Derrida's (1978) deconstruction approach, this study shows that meanings that appear stable in the source text can actually be dismantled and reinterpreted in the target text, revealing how the structure of the target language and the translator's ideological choices can influence the final form of a narrative. Subsequent translation studies are expected to open up more space for foreignization strategies, especially when dealing with texts that rely on emotional and symbolic nuances